An integration of mobile motion prediction with dedicated solicitation message for seamless handoff provisioning in high speed wireless environment - Naimah, Yaakob; Farhat, Anwar; Zeldi, Suryady (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org